Water needs and equivalence relations for different irrigated crops in the São Francisco basin (Revista Ciência Agronômica, 2018)
The present work was performed by applying the principal component analysis, in order to compare thewater needs of banana, mango, grape, sugarcane, maize and beans crops in different regions of the São Francisco riverbasin, aiming to identify the climate elements that most influence the reference evapotranspiration (ET0) in the locationsof Pirapora-MG, Jaíba-MG, Barreiras-BA and Petrolina-PE. In addition, the locations with more similarities, accordingto the evaluated parameters, were verified by applying cluster analysis, and the equivalence relations between thestudied crops were determined by integrating the parameters related to the climatic elements and the characteristics ofcrops and soils. Based on the principal components analysis, it was observed that the most significant climate elementsfor ET0estimation were different for each place. The model with two components explained 90%, 88%, 95% and 97% ofthe total variance, respectively for the locations of Pirapora, Jaíba, Barreiras and Petrolina. Because it is in a semi-aridclimate region, Petrolina showed high crop water needs, a behavior proven with the cluster analysis. The equivalence relationsallowed comparing the water needs for the studied crops, providing, in general terms, a parameter comparison between thecrops, and specifying which one will be more adequate depending on the water availability in the São Francisco basin.